Analysis of the People's Needs for Museum Tourism as Cultural Expressions and Freedom to Learn in the Post-Pandemic Era - Yuliantri, Rhoma Dwi Aria; Sudarmadi, Tular; Suwignyo, Agus (MOZAIK HUMANIORA, 2022)
The Covid-19 pandemic has impacted people's lives, including the tourism and education sectors such as tours in museums. This study aims to answer three questions (1) How high is the priority of the community's needs for post-pandemic museum tourism? (2) What are the museum tourism needs in terms of museum facilities, cultural activities and independent learning programs? (3) What are the public opinions on the tourism program that should be developed by the museum to respond to the priority needs of museum tourism after the pandemic? This research was conducted using quantitative methods with descriptive statistical calculations. The results of the study showed that most of the respondents strongly agreed (79.13%) and agreed (18.26%) that museum visits should be based on the spirit of finding alternative places to learn and seek new knowledge. Respondents decided to visit a museum firstly due to the programs offered by the museum. Regarding museums which employed freedom to learn program, respondents agreed (53.04%) if museums promoted various activities as learning arenas based on the government programs. Respondents' expectations of post-pandemic museums lead to the concept of "museums for community.” This means that museum management and the development of cultural creations potential and economic activities by museums are welcomed with high interest if the people or community are involved. It is suggested that museum managements (1) organize cultural performance acitivities as part of the promotion for museum visits, and (2) engage with local communities in the creation and implementation of the activities.